Laparoscopic Cholecystectomy in Cases of Acute Cholecystitis - Muhammad Aslam, Munawer Latif Memon, Dileep Kumar, Tayyaba Rasheed, Abdul Rasheed Zai (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate the laparoscopic cholecystectomy procedure in cases of acute cholecystitis. Study Design: Cohort study Place and Duration of Study: Department of Surgery, Surgical Unit-1, SIMS/Services Hospital Lahore from 1st January 2021 to 30th June 2022. Methodology: One hundred and ninety eight cases which suffered from acute cholecystitis were enrolled. The age of the cases was within 35-60 years. The cases were divided into 3 groups; group A, group B and group C. The group selection was dependent on the interval period (between the onset of acute attack and the time of presentation for treatment). Group A was the one where interval period was <3 days, Group B has 3 to 7 days while it was >7 days in group C. The laparoscopic cholecystectomy was performed and operative outcomes were evaluated. Results: The mean age of the patients was 40.66±1.5 years with more females in each group than males. The cases of gall bladder empyema/mucocele were presented at the highest 68.8%. This was followed by the cases having Gall Bladder phlegmon identified in 24.74% of the cases. The rate of complication was highest in Group B while operation time and post-operative hospital stay was highest in Group A. The conversion rate from Laparoscopic to open cholecystectomy was measured as 3.03%. Conclusion: Laparoscopic cholecystectomy is a procedure which can be successfully achieved in acute cholecystitis cases with reduced conversion rate and complication attained through surgical expertise. Keywords: Laparoscopic cholecystectomy, Acute cholecystitis, Conversion rate